Orally available soluble epoxide hydrolase/phosphodiesterase 4 dual inhibitor treats inflammatory pain - Blöcher, René (J Med Chem, 2018)
Inspired by previously discovered enhanced analgesic efficacy between soluble epoxide hydrolase (sEH) and phosphodiesterase 4 (PDE4) inhibitors, we designed, synthesized and characterized 21 novel sEH/PDE4 dual inhibitors. The best of these displayed good efficacy in in vitro assays. Further pharmacokinetic studies of a subset of 4 selected compounds led to the identification of a bioavailable dual inhibitor N-(4-methoxy-2-(trifluoromethyl)benzyl)-1-propionylpiperidine-4-carboxamide (MPPA). In a lipopolysaccharide induced inflammatory pain rat model, MPPA rapidly increased in the blood (T(max) = 30 min; C(max) = 460 nM) after oral administration of 3 mg/kg and reduced inflammatory pain with rapid onset of action correlating with blood levels over a time course of 4 hours. Additionally, MPPA does not alter self-motivated exploration of rats with inflammatory pain or the withdrawal latency in control rats.